A Sociolinguistic Investigation of Anglicisms in Personal and Business Names in the Yorùbá Speech Community (2011)
Anglicisation, a major way by which the Yoruba compromise their cultural values, is paradoxically a significant process of domesticating English in Nigeria. Although a large body of literature exists on names, the recent Anglicising tendencies among the Yoruba are yet to be studied despite the strong implications of the phenomenon for the Yoruba language. This study, therefore, examined Yoruba Personal Names (YPNs) and Yoruba Business Names (YBNs), the two mostly affected onomastic genres, with a view to revealing the sociolinguistic significance of such names among Yoruba-English bilinguals (YEBs). The study adopts Labov‟s Variability Theory, which accounts for variety differentiations, changes, modifications and environmental influences. The six states in South-western Nigeria, and parts of Kwara, Kogi, and Edo were purposively sampled. Data were obtained through observation, interview, and survey questionnaire. Four hundred copies of an open-ended questionnaire were administered to randomly selected respondents. Two hundred shop owners with Anglicised names on their billboards were randomly selected and interviewed. Nine domains of discourse were examined: billboards, vehicles, business cards, wedding cards and „pray-for-us‟ letters, e-mail addresses, mementoes, official documents, television/newspapers and goods. The survey questionnaire was analysed through percentage frequency and distributions. Other documents were content-analysed. Four varieties of Anglicisms were identified in YPNs and YBNs namely, consanguinity-indicative Anglicisms, individualised Anglicisms, multiple culture-indicative Anglicisms, and Arabic-Yoruba Anglicised names. These Anglicisms underwent graphological, phonological and lexico-semantic changes. At the graphological level, the English letter “h” was inserted into word initial positions to realise the voiceless palato-alveolar fricative “/ʃ/”. At the phonological level, the English “cc” phonotactic form was imposed on the Yoruba bilabial plosive; and English consonants were transposed. At the lexico-semantic level, English affixes were deployed at word initial, medial and final positions. English sounds were imposed on blends of two or more Yoruba morphemes. Clipping took four forms: Clips with suffixation, clips without suffixation, clips with blending and clips with duplication. Initialling and Partial Acronymy exploited corresponding English orthographic and phonological elements. The Anglicisation of YPNs and YBNs produced the Englishness of the names. Bearers of Anglicised YPNs employed them for special reasons which revealed affection, familiarity, rapport, jocularity, prestige, elegance, and jollity. Users of Anglicised YBNs claimed they enhanced them socially and economically. Generally, YEBs preferred the Anglicised names to their indigenous names because they believed they had prestige and elegance. Varieties of Anglicisms at the graphological, phonological and lexico-semantic levels revealed a considerable alteration of Yoruba personal and business names. YEBs positive dispositions to the names, despite their eroding effect on Yoruba names and culture reflect a strong institutionalisation of English in Nigeria.